Keanekaragaman Jenis Ikan di Bendungan Pengga Kabupaten Lombok Tengah - Sari Lailatul Hikmah; Sri Nopita Primawati; Ismail Efendi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The purpose of this study is to determine the diversity of fish species in the Pengga Dam. The type of research used is descriptive and exploratory. The research population is all types of fish found in the Pengga Dam, and the research sample is the type of fish caught by fishermen in the Pengga Dam. The data collection techniques in this study were carried out by observation, sampling, morphological analysis techniques based on literature reviews, documentation, and collection. The data on fish types that have been obtained are continued to calculate the diversity index using the Shannon-Wiener diversity index formula (Hʹ = -∑pi ln pi). Based on the data from the research results, a total of 381 individuals were obtained from 5 points with 3 takes, and identified in a total of 4 species (Oreochromis niloticus, Pterygoplichthys multiradiatu, Channa striata, and Barbonymus gonionotus) which belong to 2 classes (Actinopterygii and Osteichthyes), 3 orders (Peciformes, Siluformes, and Cypriniformes), 4 families (Chichlidae, Loricariidae, Channidae, and Cyprinidae), 4 genera (Oreochromis, Pterygoplichthys, Channa, and Barbonymus). From the results of the data analysis, it can be concluded that the index of fish species diversity in the Pengga Dam with three sampling times is classified as low.